The Evolving Socioeconomic Impacts of COVID-19 in Four African Countries - Furbush, Ann; Josephson, Anna; Kilic, Talip; Michler, Jeffrey D. (World Bank, Washington, DC, 2021)
The paper provides evidence on the evolving socioeconomic impacts of the COVID-19 pandemic among households in Ethiopia, Malawi, Nigeria, and Uganda. The data allow estimating the immediate economic impacts of the pandemic, beginning in April 2020, and tracking how the situation evolved through September 2020. Although households have started to see recovery in income, business revenues, and food security, the gains have been relatively modest. Additionally, households have received very little outside assistance and their ability to cope with shocks remains limited. School closures have created a vacuum in education delivery and school-aged children have struggled to receive education services remotely.